ANALYSIS OF SHRINKAGE PERFORMANCE OF U-SHAPED RUBBER OUTER WINDSHIELD OF HIGH-SPEED TRAIN AT LOW TEMPERATURE - GU Cheng; XU Lei; YU Chengtao; WANG Jiazheng (Jixie qiangdu)
Based on the low temperature tensile test data of the rubber, Ansys software was used to fit the Mooney-Rivlin hyperelastic constitutive model of rubber material parameters, and the thermo-solid coupling simulation was carried out on the U-shaped rubber outer windshield according to three real working conditions, and the influence of different working conditions on the U-shaped rubber deformation was studied.The low temperature test was carried out on U-shaped rubber outer windshield and three rubber samples with different batten thicknesses， the influence of temperature and batten thickness on its deformation was studied.The results show that the U-shaped rubber deformation is mainly caused by the temperature change, the U-shaped rubber height decreases obviously, and the shape variable of the side wall thickness and the rubber length is small.In addition, the batten thickness has a greater influence on the rubber shape variable at the bolt hole.Compared with the batten of 5 mm and 6 mm thickness, the 4 mm batten produces a larger deformation under the bolt preload action, resulting in a larger deformation at the bolt hole, and then increasing the batten thickness can effectively reduce the hole removal risk.Comparing the finite element simulation data with the low temperature test results, it is found that the two results are basically consistent，which indicates the finite element analysis feasibility and the low temperature test reliability.The research results provide some guidance basis for the U-shaped rubber outer windshield under low temperature application reliability.